Body Image Disorders and Surgical Timing in Patients Affected by Poland Syndrome: Data Analysis of 58 Case Studies. Issue 4 (April 2016) - Baldelli, Ilaria; Santi, Pierluigi; Dova, Laura; Cardoni, Gaia; Ciliberti, Rosagemma; Franchelli, Simonetta; Merlo, Domenico F.; Romanini, Maria V.
Abstract : Background: Poland syndrome is a congenital anomaly of pectoralis muscles, breast, chest, and upper arm. Several studies have reported that patients affected by chest wall deformities often experience body image disorders and decreased quality of life. Cosmetic corrective surgery is generally postponed until physical development is achieved, and latissimus dorsi flap surgery is usually suggested. This study aims to propose a new surgical timing for these patients. Methods: Patients affected by Poland syndrome ( n = 58) and control patients ( n = 50) were included in the study, and their body-related psychopathology was evaluated through the Body Uneasiness Test, a valuable multidimensional tool for the clinical assessment of body uneasiness. The Global Severity Index and several subscales were considered. Age and surgical status were taken into account. Results: Significant differences were detected between Poland syndrome patients and controls with respect to all Body Uneasiness Test subscales. Among subjects aged younger than 20 years, the group of patients not operated on was the most affected, whereas the group of peers after surgery showed scores similar to those detected in the control group. Conclusions: Surgical planning for patients with Poland syndrome should start in the period of growth to allow proper body image stabilization. Current surgical options allow for reduction of the use of invasive interventions such as the latissimus dorsi flap, in favor of less invasive surgical techniques such as expanders, implants, and autologous fat grafting. This new surgical timing will help to ameliorate problems with physical and mental development. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.